ANALISIS RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2014-2019 - Harry Patuan Panjaitan; Fyter Tanjaya (Procuratio : Jurnal Ilmiah Manajemen, 2021)
The rate of population growth from year to year is always increasing which causes the level of public consumption to increase. But the movements in the food and beverages sector's share price index showed a flat fluctuating chart. The objective of this study is to analyze of financial performance of companies influence that focus on Return On Assets (ROA), Debt to Equity Ratio (DER), Price Earning Ratio (PER) and Total Assets Turnover (TATO) of the return on company stock shares in Food and Beverages’ sector period 2014-2019 by manufactur’s company. The population becomes object of this research is manufactur’s company sector food and beverages period of years of 2014-2019 amounted of 26 companies. Amount sample the used is the 12 food and beverages company listed on the IDX that publish an annual report for 2014–2019 and still stand up duraing period of perception and also publicized of year of 2014-2019. The analysis method used in this research that is with multiple linear regression analysis. The result of the study shows Return On Assets (ROA), Debt to Equity Ratio (DER), and Price Earning Ratio (PER) does not have an effect on return of shares in Food and Beverages’s sector by the manufactur’s company. And Total Assets Turnover (TATO) has significant positive to the return of a share in the Food and Beverages’ sector by the manufactures company. Tingkat pertumbuhan penduduk dari tahun ke tahun selalu meningkat yang menyebabkan tingkat konsumsi masyarakat meningkat. Namun pergerakan index harga saham sektor food and beverages menunjukkan grafik fluktuasi datar. Penelitian ini bertujuan untuk menganalisis tentang bagaimana pengaruh kinerja keuangan perusahaan yang difokuskan pada Return On Assets (ROA), Debt to Equity Ratio (DER), Price Earning Ratio (PER) dan Total Assets Turnover (TATO) terhadap return saham pada perusahaan manufaktur sektor food and beverages periode 2014-2019. Populasi yang menjadi obyek dalam penelitian ini adalah Perusahaan Manufaktur sektor Food and Beverages periode 2014-2019 yang berjumlah 26 perusahaan. Jumlah sampel yang digunakan dalam penelitian ini adalah 12 perusahaan food and beverages yang ada di BEI tahun 2014-2019. Metode analisa yang digunakan dalam penelitian ini dengan analisis regresi berganda. Hasil penelitian menunjukkan bahwa Return On Assets (ROA), Debt to Equity Ratio (DER), dan Price Earning Ratio (PER) tidak berpengaruh terhadap return saham sektor food and beverages dan Total Assets Turnover (TATO) mempunyai pengaruh yang positif dan signifikan terhadap return saham perusahaan manufaktur sektor Food and Beverages.